2014
DOI: 10.14319/ijcto.0202.8
|View full text |Cite
|
Sign up to set email alerts
|

The expression of p53 and hsp70 proteins after treatment with Annona muricata Linn leaf for activating apoptotic and lead to homeostasis program of Raji cells

Abstract: Purpose: Organic extracts of plant Annonaceae enhances apoptosis in animal cells and get the drives to reach a new homeostasis. The incidence rate of nasopharyngeal cancer in Indonesia is quite high. Protein 53Kd (p53) play a role in apoptosis process, being heat shock protein 70 (hsp70) play a role in homeostasis. The aim of this research is to identify the apoptotic effects of Annona muricata Linn leaf toward Raji cells by observing the p53 and hsp70 expression. Methods: Apoptotic assay was performed in 24 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…8 Another study reported that soursop leaves extracts were known to increase expression of p53 gene and lower hsp70 expression, resulted in activation of apoptosis process and stable homeostasis in Raji cells. 9 However, research about cytotoxicity of Annona muricata leaves originating from Indonesia against cervical cancer are still limited. Therefore, this research aimed to analyze cytotoxicity of A.muricata leaves against cervical cancer because it is the leading cause of cancer-related death.…”
Section: Introductionmentioning
confidence: 99%
“…8 Another study reported that soursop leaves extracts were known to increase expression of p53 gene and lower hsp70 expression, resulted in activation of apoptosis process and stable homeostasis in Raji cells. 9 However, research about cytotoxicity of Annona muricata leaves originating from Indonesia against cervical cancer are still limited. Therefore, this research aimed to analyze cytotoxicity of A.muricata leaves against cervical cancer because it is the leading cause of cancer-related death.…”
Section: Introductionmentioning
confidence: 99%
“…M Pai et al found that soursop extract has antimicrobial and fungicidal properties when used against oral microbiota [9]. Another study conducted by Astirin et al reported that extract of A. muricata activates the apoptosis process due to an increase in p53 expression in a cancer environment [10]. Padma et al showed that ethanolic extract of A. muricata caused a reduction in lipid peroxidation and increased protective effects against oxidative stress induced by carbon tetrachloride.…”
Section: Introductionmentioning
confidence: 99%
“…Efek antikanker ekstrak etanolik daun sirsak diduga berkaitan dengan kandungan senyawa acetogenin dan flavonoid daun sirsak. Efek antikanker daun sirsak dapat terjadi melalui beberapa mekanisme di antaranya menghambat proliferasi, 15,23 menginduksi apoptosis, 23 meningkatkan ekspresi p53, 24 dan melalui aktivitas antioksidan. 13 Analisis statistik data hasil penelitian menunjukkan tidak terdapat perbedaan terjadinya displasia ringan yang bermakna antara kelompok tikus yang diinduksi DMBA dengan kelompok tikus yang diinduksi DMBA dan diberi ekstrak etanol daun sirsak 100 mg/kg BB dan 200 mg/kg BB.…”
Section: Hasil Penelitianunclassified